First report of a new Carlavirus provisionally named rose virus B and apple mosaic virus in mixed infections of Rosa sp. in Mexico - Ortega-Acosta, Candelario; Ochoa Martínez, Daniel L; Diaz-Lara, Alfredo (Plant disease, 2024)
Rose (Rosa sp.) is an important ornamental plant in the cut flower industry around the world. This species is prone to hosting several viruses since it is propagated vegetatively, mainly by grafting (Mollov et al., 2013). In 2021, rose plants of unidentified variety with mosaic, vein yellowing, chlorotic line patterns, and interveinal chlorosis were observed in a rose plantation established in open field in Temixco, Morelos (Supplementary Figure 1). To determine the cause of symptoms was due to viral infection, nucleic acids were extracted from leaves by in-house CTAB procedure and DNase treated. A pooled RNA sample extracted from 4 symptomatic plants was sent to BGI Genomics (China) for high-throughput sequencing (HTS). A stranded mRNA library was prepared and sequenced on the DNBSEQ platform (BGI). A total number of 13,646,715 paired 150-bp clean reads were generated. The reads were assembled de novo into 79,309 contigs ranging from 78 to 15,817 nucleotides (nt) using SPAdes (Prjibelskiet et al., 2020). The contigs were subjected to BLASTx and BLASTn for annotation. A contig with a length of 8,842 nt (208x average coverage per nt) showed 90.6% identity to rose virus B (RVB) (MT473961), and was deposited in GenBank under accession number ON165234. Additionally, three contigs (ON165235-ON165237) corresponding to RNA1 (3,443 nt; 154x coverage), RNA2 (2,938 nt; 231x coverage), and RNA3 (1,897 nt; 232x coverage) of apple mosaic virus (ApMV) were identified. These contigs showed up to 98.4%, 89.7%, and 98.6% identity, respectively, to each corresponding RNA sequences of ApMV. No other viral sequence was identified from the constructed contigs. Subsequently, the presence of RVB was confirmed by RT-PCR performed with an aliquot of the pooled RNAspan style="font-family:'Times New Roman'; font-size:11pt"> with specific primers targeting the replicase and CP (Diaz-Lara et al., 2021). For ApMV, a new set of primers were designed: ApMV_RNA1F (5'-AAATCTCCCGAAAGGGCCTG-3')/ApMV_RNA1R (5'-TCACTCGTCGCATGGATGGATAGC-3'), ApMV_RNA2F (5'-TTGGTACGAGTCGTGGTTGGTTGG-3')/ApMV_RNA2R (5'-GGAAAACTGACCGCAAACCC-3'), and ApMV_RNA3F (5'-GGAGGTTAGAGGCCCGAATG-3')/ApMV_RNA3R (5'-CGCACAGGTGGTAACTCACT-3') which amplify segments of 444 bp, 546 bp, and 434 bp, respectively. The amplicons obtained for both viruses were subjected to Sanger sequencing, confirming the identity of RVB and ApMV. The sequences from the RVB replicase (ON165241) and CP (ON165240) showed 93.9% and 97.0% nt identity with an RVB isolate reported in the USA (MT473961). On the other hand, sequences from RNA1 (ON165238), RNA2, (OP413436), and RNA3 (ON165239) of ApMV had 99.2%, 89.2%, and 99% nt identity, respectively. Finally, the four symptomatic plants were individually tested by RT-PCR to identify RVB and ApMV. Interestingly, both viruses were detected in all the plants analyzed. ApMV (genus Ilarvirus) is associated with mosaic and mottling symptoms in rose (Thomas, 1984). It has been accepted that ApMV is present in rose plants in Mexico (Cardenas-Alonso, 1994), with no evidence to confirm it. RVB was identified in rose in USA, and this virus was classified as a new species of the genus Carlavirus (Diaz-Lara et al., 2021). In addition to RVB, rose virus A and rose virus C have also been reported in rose; however, the symptomatology linked to these viruses is unknown (Xing et al. 2021; Diaz-Lara et al., 2020). Recently, RVB and ApMV were reported in rose plants in Taiwan (Chen et al., 2022). To our knowledge, this is the first report of RVB and ApMV in a mixed infection in rose in Mexico.